2020
DOI: 10.1186/s13750-020-00199-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of wildlife translocations in protected areas: what is the type and extent of existing evidence? A systematic map protocol

Abstract: Background Conversion, fragmentation, and loss of natural habitats are among the main causes of declining species’ populations worldwide. Protected areas are therefore crucial for biodiversity as they provide refuge and ensure key ecological processes. Wildlife translocations, defined as “the deliberate movement of organisms from one site for release in another”, have been used in conjunction as a conservation tool for a number of decades as wild populations become increasingly fragmented and endangered. Not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…This systematic map followed the detailed methods described in the a priori systematic map protocol [60]. It was performed in strict concordance with the guidelines provided by The Collaboration for Environmental Evidence [61], and conforms to the ROSES reporting standards (see Additional file 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This systematic map followed the detailed methods described in the a priori systematic map protocol [60]. It was performed in strict concordance with the guidelines provided by The Collaboration for Environmental Evidence [61], and conforms to the ROSES reporting standards (see Additional file 1).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, before being able to perform concrete quantitative syntheses on the effectiveness of wildlife translocations, RNF requested a comprehensive catalogue of existing literature describing the links between different types of wildlife translocation interventions and the factors that may be important to consider before implementation. Several further meetings were held, (refer to protocol [60] for full details), providing reserve managers the opportunity to contribute to the coding and data extraction decisions/procedures (notably the definition of variables). Following the acceptance of the protocol, further dialogue with managers enabled decisions to be made on the form and content of a practitioner brief, which will provide a summary of key results in an operational manner in order to aid decision-making.…”
Section: Stakeholder Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Translocation is a critical tool, often used in addressing challenges bordering not only on stray wildlife, but wildlife management in general. It is the deliberate capture, transporting and releasing of the captured wildlife into another ecological environment or back to their natural habitats in the case of stray wildlife [29]. Thus, it is a major wildlife management tool that can also be used in restocking or rewilding of depleted protected areas, including stocking of game ranches and zoos to assist in management of threatened native species [30].…”
Section: Wildlife Capture and Translocation: Taking Advantage Of Vete...mentioning
confidence: 99%
“…The only two mitigation measures not evaluated by any study that we identified were translocations and fencing. The use of translocations as a conservation tool is a contentious issue; they are costly to execute and offer variable results due to the different factors that can determine their success (Sherman et al., 2020; Langridge et al., 2020). In Arunachal Pradesh, India, “a few isolated groups” of eastern hoolock gibbons ( Hoolock leuconedys ) were translocated from unprotected forest fragments disturbed by road construction and permanent human settlement to the Mehao Wildlife Sanctuary, although they have not yet been monitored since (Kumar et al., 2013).…”
Section: Mitigation Measuresmentioning
confidence: 99%